2003
DOI: 10.1002/cncr.11487
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of osteopontin is associated with intrahepatic metastasis, early recurrence, and poorer prognosis of surgically resected hepatocellular carcinoma

Abstract: BACKGROUNDIntrahepatic metastasis via portal vein spread is an important feature and a crucial unfavorable prognostic factor of hepatocellular carcinoma (HCC). To identify the molecular factors for tumor progression, the authors used differential display (DD) to analyze aberrant gene expression in HCC. The goal of the current study was to elucidate the clinicopathologic and prognostic significance of osteopontin (OPN) in HCC progression.METHODSOPN mRNA levels, which were increased preferentially in HCC in a DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
233
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(247 citation statements)
references
References 88 publications
9
233
2
1
Order By: Relevance
“…39 Here we showed that tumor stage closely correlated with patient's survival (p Ͻ 0.0001), and minute HCC (Յ 2 cm) with encapsulation and no vascular invasion was a unique group of HCC with an excellent prognosis (Fig. 2).…”
Section: Prognostic Significances Of High Afpmentioning
confidence: 57%
“…39 Here we showed that tumor stage closely correlated with patient's survival (p Ͻ 0.0001), and minute HCC (Յ 2 cm) with encapsulation and no vascular invasion was a unique group of HCC with an excellent prognosis (Fig. 2).…”
Section: Prognostic Significances Of High Afpmentioning
confidence: 57%
“…OPN is an ECM protein that is considered as the third marker for matrix deposition (Pan et al 2003). Abu El Makarem et al (2011) found a significant elevation in OPN levels in patients with HCV-related HCC.…”
Section: Discussionmentioning
confidence: 99%
“…OPN is an integrin-binding glycophosphoprotein that is expressed by several cell types and especially by transformed malignant epithelial cells. Additionally, OPN is believed to be involved in many physiological cellular functionsespecially in the regulation of migration, invasion and thus metastasis as well as in the survival of tumour cells (Pan et al 2003). doi: 10.1590/0074-0276130139These biomarkers have been analysed individually and in combination to assess the severity and progression of hepatic fibrosis and to follow-up changes related to viral treatment (Saitou et al 2005, Sanvisens et al 2009, Parkes et al 2011).…”
mentioning
confidence: 99%
“…In contrast, in a study of a series of 240 hepatocellular carcinomas, elevated OPN RNA levels were associated with high grade, late stage and early recurrence, which are all associated with poor patient prognosis (Pan et al, 2003). In an expression array study of 60 colorectal tumours, representing a range of stages from adenomas, Astler Collier stages B, C and D, and liver metastases, OPN was identified as the lead marker that was most consistently upregulated with tumour progression (Agrawal et al, 2002).…”
Section: Opn Expression In Human Tumours: Potential Utility As a Tumomentioning
confidence: 98%